EXPERIENCE OF INTRODUCING ISLAMIC BANKING OF FOREIGN COUNTRIES (American Journal of Interdisciplinary Research and Development, 2023)
This article discusses the experience of introducing islamic banking of foreign countries, analyzes the current state of the global islamic finance industry, including the countries, such as Malaysia, Indonesia, and Turkey, which have chosen the approach of a binary banking system.